2017
DOI: 10.2527/jas.2016.1046
|View full text |Cite
|
Sign up to set email alerts
|

Effect of expeller extracted canola meal on growth performance, organ weights, and blood parameters of growing pigs

Abstract: The aim of this study was to assess the effects of increasing levels of expeller extracted canola meal (EECM) in diets for growing pigs on performance, gastrointestinal tract weight, thyroid gland weights, blood plasma concentration of triiodothyronine and tetraiodothyronine, red blood cell count, hemoglobin content in blood, and hematocrit. Four diets were fed to 48 pigs (19.9 ± 1.60 kg initial BW) in 24 pens (6 pens per diet) for 4 wk in a completely randomized design. The diets were a control corn-soybean m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
15
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 23 publications
6
15
4
Order By: Relevance
“…The total aliphatic glucosinolate value (7.8 µmol/g) for CPCC was comparable to the values that were reported by Parr et al (2015; 5.9 µmol/g) for SECM and by Velayudhan et al (2017;7.5 µmol/g) for EPCM. However, the total indolic glucosinolate value (6.6 µmol/g) for CPCC fed in the current study was greater than the values that were reported by Parr et al (2015; 2.8 µmol/g), and Newkirk et al (2003; 4.8 µmol/g) for SECM, and by Velayudhan et al (2017; 1.4 µmol/g), and Woyengo et al (2011; 2.8 µmol/g) for EPCM. Jensen et al (1995) reported a greater reduction in the indolic glucosinolate content than in the aliphatic glucosinolate content in rapeseed meal due to toasting.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The total aliphatic glucosinolate value (7.8 µmol/g) for CPCC was comparable to the values that were reported by Parr et al (2015; 5.9 µmol/g) for SECM and by Velayudhan et al (2017;7.5 µmol/g) for EPCM. However, the total indolic glucosinolate value (6.6 µmol/g) for CPCC fed in the current study was greater than the values that were reported by Parr et al (2015; 2.8 µmol/g), and Newkirk et al (2003; 4.8 µmol/g) for SECM, and by Velayudhan et al (2017; 1.4 µmol/g), and Woyengo et al (2011; 2.8 µmol/g) for EPCM. Jensen et al (1995) reported a greater reduction in the indolic glucosinolate content than in the aliphatic glucosinolate content in rapeseed meal due to toasting.…”
Section: Discussionsupporting
confidence: 85%
“…Glucosinolates are heat-liable and hence degradable by heat (Newkirk and Classen, 2002). The total aliphatic glucosinolate value (7.8 µmol/g) for CPCC was comparable to the values that were reported by Parr et al (2015; 5.9 µmol/g) for SECM and by Velayudhan et al (2017;7.5 µmol/g) for EPCM. However, the total indolic glucosinolate value (6.6 µmol/g) for CPCC fed in the current study was greater than the values that were reported by Parr et al (2015; 2.8 µmol/g), and Newkirk et al (2003; 4.8 µmol/g) for SECM, and by Velayudhan et al (2017; 1.4 µmol/g), and Woyengo et al (2011; 2.8 µmol/g) for EPCM.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In Denmark, 0.5 mio. tons rapeseed is produced (FAOSTAT, ), and RPC is a potential protein source for growing pigs (Danielsen, Eggum, Jensen, & Sørensen, ; Velayudhan, Schuh, Woyengo, Sands, & Nyachoti, ). Rapeseed meal (RM) is, however, the main co‐product produced in Europa, where the rapeseed production amounts to 22 mio.…”
Section: Introductionmentioning
confidence: 99%